Variations in the Patterns of Dermatoglyphics amongst Twins- An Observational Study - R. Ravi Sunder; P. Neelima (Innovations in Science and Technology Vol. 3, 2022)
Identical twins were thought to share most of the features in common. Dermatoglyphics (from ancient Greek derma=skin, glyph=carving) is the scientific study of fingerprints. The ridges and groves on palms and soles are under the influence of genes and are unique. Palmar and finger dermatoglyphics are formed between the 10th and the 17th weeks of gestation and their morphology can be influenced by genetic or environmental factors, interfering with normal intrauterine development. The aim of the present study is to determine the dermatoglyphic patterns in twins-both monozygotic and dizygotic and to observe the extent to which they share between them. After receiving informed verbal consent from three pairs of twins, the fingerprint patterns were analysed from the images captured. The results of two pairs of dizygotic twins (one pair females and one pair males) and one pair monozygotic twins (females) were as follows: 1st pair-: The patterns on the left hand did not match at all, but three fingers on the same hand demonstrates similar patterns.2nd pair-: The dermatoglyphics of two fingers of the right hand and three digits of the left hand were the same. Patterns of the remaining digits were not identical.3rd pair-: The evaluation of dizygotic males revealed the same pattern of two digits on the left hand but no digits on the right hand were identical. The current study found that the patterns were identical on a few digits but different on the rest. This study could be improved by evaluating a larger number of twins.